Reductions in childhood pneumonia mortality after vaccination in the United States - Paternina-Caicedo, A; Smith, A; Buchanich, J; Garcia-Calavaro, C; Alvis-Guzman, N; Narvaez, J; de Oliveira, L; De la Hoz-Restrepo, F (Lippincott, Williams & Wilkins, 2023)
Background: We aim to estimate the magnitude of the reduction in pneumococcal pneumonia and meningitis mortality after the mass introduction of pneumococcal conjugate vaccine (PCV)7 and PCV13 in children in the United States.